Analisis SWOT pada Strategi Pengembangan Pantai Cuko Kabupaten Kaur - Vilami, Florience; Yanto, Hernowo Novi; Harmiati, Harmiati (Lembaga Yasin AlSys, 2025)
Cuko Beach in Kaur Regency is a local tourism destination with high natural potential that has not yet been optimally utilized. In the context of tourism sector growth in Indonesia, it is essential to formulate a development strategy based on a comprehensive analysis of the destination’s conditions. This study aims to analyze the development strategy of Cuko Beach using a descriptive qualitative approach through SWOT analysis. Data were collected through observation, in-depth interviews with the village head, fishermen, visitors, and local residents, as well as field documentation. The analysis involved identifying internal factors such as strengths and weaknesses, along with external factors including opportunities and threats. The findings reveal that the main strengths of Cuko Beach lie in its scenic coastal landscape, unique rock formations, and ecotourism potential. However, significant weaknesses include limited supporting tourism facilities, low levels of community participation, and inadequate access infrastructure. There are considerable opportunities for local economic development through marine and culinary tourism, although threats such as environmental degradation and competition from nearby destinations remain challenges. The study concludes that the development strategy for Cuko Beach must be holistic and sustainable, emphasizing community involvement, infrastructure improvement, and environmental conservation. These findings contribute to the academic discourse on sustainable tourism development and may serve as a reference for local destination management policy formulation.